383 First-in-man clinical trial of intratumoral injection of clostridium Novyi-NT spores in combination with pembrolizumab in patients with treatment-refractory advanced solid tumors. (9th November 2020) - Janku, Filip; Fu, Siqing; Murthy, Ravi; Karp, Daniel; Hong, David; Tsimberidou, Apostolia; Gillison, Maura; Adat, Abha; Raina, Anjali; Call, Greg; Kreider, Brent; Tung, David; et al.
Abstract : Background: Intratumorally injected Clostridium novyi-NT (non-toxic), an attenuated strain of C. novyi that lacks production of the lethal alpha toxin, replicates within hypoxic tumor regions and elicits tumor-confined cell lysis. Early clinical and translational data suggest that intratumoral injection of C. novyi-NT is feasible, demonstrates early signals of anti-tumor activity and induction of the host immune response, which supports additional studies in combination with immune checkpoint inhibitors. Methods: This first-in-human study (NCT03435952 ) enrolls patients with injectable, treatment-refractory solid tumors to receive a single intratumoral injection of C. novyi-NT across 4 dose cohorts (3 × 104 to 100 × 104 spores, 3+3 dose-escalation design) in combination with intravenous pembrolizumab 200 mg every 3 weeks for up to 24 months to determine dose-limiting toxicities (DLTs), and the maximum tolerated dose (MTD). Results: As of August 24, 2020, 9 patients (breast cancer, n=2; colorectal cancer, n=1; fibrous histiocytoma, n=1; anal cancer, n=1; chondrosarcoma, n=1; appendiceal cancer, n=1; tongue squamous cell cancer, n=1; nasopharyngeal cancer, n=1) were treated. There were no DLTs to date. Signs and symptoms of C. novyi-NT germination (infection) including fever, injection site pain, erythema, swelling, tenderness, and in some cases, ulceration, spontaneous drainage, tissue sloughing, bleeding, and malodor were observed in 5 patients. Partial responses were noted in 2 of 9 patients (tongue squamous cell cancer, nasopharyngeal cancer). Conclusions: Single intratumoral injection of C. novyi-NT in combination with pembrolizumab has been demonstrating manageable toxicity profile and encouraging signals of anticancer activity. The enrolment continues. Trial Registration: NCT03435952 Ethics Approval: The study was approved by MD Anderson IRB